Cold plasma enhanced preparation of high performance PdRu/C formic acid dehydrogenation catalysts. (3rd November 2021) - Di, Lanbo; Zhang, Jingsen; Zhang, Xiuling; Xia, Guangqing; Hua, Yue; Li, Hong; Zhang, Yuzhuo
Abstract: A facile and environment-friendly atmospheric-pressure cold plasma treatment method was adopted to synthesize activated carbon supported bimetallic PdRu catalysts (PdRu/C–P) toward formic acid (FA) dehydrogenation. The results showed that the PdRu/C–P with a Pd/Ru mass ratio of 9/1 exhibited the highest activity featuring total gas volume of 337.2 ml during 4 h and initial turnover frequency (TOF) value of 954.2 h −1 . In comparison with the PdRu/C-T catalyst prepared by thermal reduction, enhanced FA dehydrogenation activity of the PdRu/C–P catalysts could be mainly attributed to the efficient electron transfer from Ru to active Pd in the PdRu alloy, and the high PdRu/C atomic ratios arising from the migration of the PdRu active species from the pores to the outer surface of the support affected by Coulomb repulsion effect in the plasma. The total gas volume generated by FA over the PdRu/C–P was decreased to 88.4% and 86.5% after the second and third reaction cycles, respectively, in comparison with the first cycle. However, they have been decreased to 64.6% and 64.4%, respectively, for PdRu/C-T prepared by thermal reduction. In addition, the performance of the PdRu/C–P is a little inferior to PdAu/C–P prepared by cold plasma, but its catalytic stability is much better than the expensive PdAu/C–P. The enhancement of catalytic stability for the PdRu/C–P catalyst is attributed to the small and stable particle size of PdRu, and less leaching of active species resulting from the strong metal-support interaction induced by cold plasma. Graphical abstract: Image 1 Highlights: PdRu/C–P towards formic acid dehydrogenation was synthesized by cold plasma. The initial TOF of PdRu/C–P is as high as 954.2 h −1 . 88.4% and 86.5% activity of first run of PdRu/C–P were retained for the second and third runs, respectively. The high stability of PdRu/C–P was due to the plasma enhanced metal-support interaction.